Analysis of determinants of coffee exports in Indonesia - Fitrah Sari Islami; Panji Kusuma Prasetyanto; Aziz Dwi Setiawan (Faculty of Economics and Business Mulawarman University, 2022)
Coffee is one of the plantation commodities that has an important role in economic activities in Indonesia. Coffee is also one of Indonesia's export commodities which is quite important as a foreign exchange earner in addition to the oil and gas sector. During 2005-2018 Indonesia's coffee exports always fluctuated every year. Therefore, there is a need for research on the factors that affect coffee exports. This study aims to analyze the effect of coffee production, plantation area and exchange rate on Indonesian coffee exports. The results show that: 1) During 2005-2018 the value of coffee exports increased by an average of 6% per year, Indonesian coffee production increased by an average of 1.2% annually, the area of coffee plantations decreased by an average of 0.1% annually and the price of the US Dollar increased by 3.1% annually; 2) Partially the variable of coffee production has a significant positive effect on coffee exports, the area of coffee plantations has a significant positive effect on coffee exports, and the exchange rate has a significant positive effect on coffee exports, while simultaneously the variables of the amount of production, the area of the plantation, and the exchange rate have an effect on coffee exports.